Analysis of Arrester Usage as Over Voltage Protection at 150 kV Mantang Substation, Indonesia - Heru Muhtari; Adel Salem Sultan; Ivan Pavkovic; Xianjie Feng; Shehab Abdulwadood Ali; Neli Velikova; Yehia Sayed Mohamed (Frontier Advances in Applied Science and Engineering, 2025)
Over time, various problems and disturbances can arise in the management of transmission and distribution systems, either from internal or external sources. One of the most significant external disturbances that can lead to equipment failure is a lightning strike, which causes a surge in overvoltage. A device commonly used to protect electrical systems from such disturbances is the lightning arrester. This study focuses on the 150 kV Embassuring Substation to analyze the ideal placement distance between the lightning arrester and the transformer, as well as to compare system behavior under normal and fault conditions. The research method involves analytical calculations, including the determination of maximum arrester distance, arriving voltage at the system, maximum transformer voltage, arrester rated voltage, lightning surge impedance, arrester discharge current, and arrester resistance. In addition, field data were simulated using ETAP software. The results show that the peak voltage caused by a lightning strike reaches 572 kV with a rise time of 0.4 µs. After 5 µs, the impulse voltage decreases to 146 kV. The maximum calculated arrester distance is 28.5 m, with an arriving voltage of 493 kV, maximum transformer voltage of 165 kV, arrester rated voltage of 132 kV, lightning surge impedance of 510 Ω, discharge current of 2.1 kA, and arrester resistance of 219.04 Ω. ETAP simulation results indicate significant waveform changes during lightning disturbances. The arrester's performance as an overvoltage protection device is considered reliable, especially with field installation at a distance of 5 m from the transformer, well within the calculated maximum protection range.